Comparison of non-invasive MRI measurements of cerebral blood flow in a large multisite cohort. Issue 7 (July 2016) - Dolui, Sudipto; Wang, Ze; Wang, Danny JJ; Mattay, Raghav; Finkel, Mack; Elliott, Mark; Desiderio, Lisa; Inglis, Ben; Mueller, Bryon; Stafford, Randall B; Launer, Lenore J; Jacobs, David R; et al.
Arterial spin labeling and phase contrast magnetic resonance imaging provide independent non-invasive methods for measuring cerebral blood flow. We compared global cerebral blood flow measurements obtained using pseudo-continuous arterial spin labeling and phase contrast in 436 middle-aged subjects acquired at two sites in the NHLBI CARDIA multisite study. Cerebral blood flow measured by phase contrast (CBFPC : 55.76 ± 12.05 ml/100 g/min) was systematically higher ( p  < 0.001) and more variable than cerebral blood flow measured by pseudo-continuous arterial spin labeling (CBFPCASL : 47.70 ± 9.75). The correlation between global cerebral blood flow values obtained from the two modalities was 0.59 ( p  < 0.001), explaining less than half of the observed variance in cerebral blood flow estimates. Well-established correlations of global cerebral blood flow with age and sex were similarly observed in both CBFPCASL and CBFPC . CBFPC also demonstrated statistically significant site differences, whereas no such differences were observed in CBFPCASL . No consistent velocity-dependent effects on pseudo-continuous arterial spin labeling were observed, suggesting that pseudo-continuous labeling efficiency does not vary substantially across typical adult carotid and vertebral velocities, as has previously been suggested. Conclusions: Although CBFPCASL and CBFPC values show substantial similarity across the entire cohort, these data do not support calibration of CBFPCASL using CBFPC in individual subjects. The wide-ranging cerebral blood flow values obtained by both methods suggest that cerebral blood flow values are highly variable in the general population.